Hospitalized with stroke at the weekend: Higher cost and risk of early death?. Issue 1 (January 2022) - Ghiani, Marco; Mueller, Sabrina; Maywald, Ulf; Wilke, Thomas
Objectives: Previous studies have shown that weekend hospitalizations are associated with poorer health outcomes and higher mortality ("weekend effect"). However, few of these studies have adjusted for disease severity and little is known about the effect on costs. This work investigates the weekend effect and its costs for patients with cerebral infarction in Germany, adjusting for patient characteristics and proxies of stroke severity. Methods: Adult patients with a cerebral infarction hospitalization 10th revision of the International statistical classification of diseases and related health problems (ICD-10: I63) between 01 January 2014 and 30 June 2017 were included from German health claims (AOK PLUS dataset). Propensity score matching was used to match patients hospitalized on weekends or on public holidays (weekend group) with patients hospitalized during the working week (workday group), based on baseline characteristics and proxies for disease severity such as concomitant diagnoses of aphasia, ataxia, and coma, or peg tube at index hospitalization. Matched cohorts were compared in terms of in-hospital, 7-day, and 30-day mortality, as well as risk and costs of stroke and rehabilitation stays in the year after first stroke. Results: Of 32, 311 patients hospitalized with cerebral infarction between 01 January 2014 and 30 June 2017, 8409 were in the weekend group and 23, 902 in the workday group. After propensity score matching, 16, 730 patients were included in our study (8365 per group). Matched cohorts did not differ in baseline characteristics or stroke severity. In the weekend group, the risk of in-hospital death (11.2%) and the seven-day mortality rate (6.8%) were 13.1% and 17.2% higher than in the workday group, respectively (both p < 0.01). The hazard ratio for death in the weekend group was 1.1 ( p = 0.043). The risks of subsequent stroke hospitalization and rehabilitation stays for a stroke were 8.4% higher and 5.5% higher in the weekend group (both p = 0.02). As a result, the stroke-related hospitalization and rehabilitation costs per patient year were, respectively, 5.6% and 8.0% higher in the weekend group (both p = 0.01). Conclusions: A significant weekend effect emerged after controlling for observable patient characteristics and proxies of stroke severity. This effect also resulted in higher costs for patients admitted on weekends.